Implementasi RT/RW-Net Menggunakan Metode User dan Bandwidth Management - Ningsih, Yuli Kurnia; Rochman, Yusuf Saeful; Kurniawati, Nazmia (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
In this paper RT / RW-Net has been designed and realized as a system to access the internet network. The system was built using the Mikrotik Router as an operating system, access point as a network distributor, and an omnidirectional antenna as transmitter and receiver of Wi-Fi signals. The user manager feature on the proxy plays a role in managing several functions such as bandwidth limitation and quota limitation. Quotas and grace periods can be made according to customer requests. The network is tested when the customer is connected to the RT / RW-Net hotspot automatically on the customer's device the RT / RW-Net page will appear to enter the username and password that has been given by the administrator. The system is tested by measuring the RSSI value (Receive Signal Strength Indicator) to determine signal quality based on applicable standards. Based on the test results, the lowest RSSI value is -65 dBm at a distance of 280m to the west with a note that there is no obstacle in the omnidirectional antenna to the customer's device. This system can also inform the remaining quota status and active period to the customer on the RT / RW-Net homepage.